(untitled) (Ustozlar uchun, 2026)
This article investigates the semantic and cultural features of wild animal symbols in the English language. Drawing on phraseological units, proverbs, heraldic tradition, and literary texts, the study identifies the principal symbolic meanings associated with the lion, fox, wolf, bear, and eagle in English cultural and linguistic tradition. The research highlights the interplay between universal and culturally specific dimensions of animal symbolism.